2011
DOI: 10.3389/fgene.2011.00062
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as New Characters in the Plot between Epigenetics and Prostate Cancer

Abstract: Prostate cancer (PCA) still represents a leading cause of death. An increasing number of studies have documented that microRNAs (miRNAs), a subgroup of non-coding RNAs with gene regulatory functions, are differentially expressed in PCA respect to the normal tissue counterpart, suggesting their involvement in prostate carcinogenesis and dissemination. Interestingly, it has been shown that miRNAs undergo the same regulatory mechanisms than any other protein coding gene, including epigenetic regulation. In turn, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Epigenetic control of PCa involves specific miRNAs that are targets, i.e., epigenetically regulated (Table 5), and/or some miRNAs directly affect enzymes and other molecules involved in epigenetic control (Paone et al 2011). Examples of miRNAs that modulate epigenetic control in PCa include miRNA-101, which inhibits the oncogenetic protein enhancer of zeste homolog 2 (EZH2) and miRNA-449a, which down-regulates histone deacetylase 1 (Varambally et.…”
Section: Mirnas and Epigenetic Control Of Pcamentioning
confidence: 99%
“…Epigenetic control of PCa involves specific miRNAs that are targets, i.e., epigenetically regulated (Table 5), and/or some miRNAs directly affect enzymes and other molecules involved in epigenetic control (Paone et al 2011). Examples of miRNAs that modulate epigenetic control in PCa include miRNA-101, which inhibits the oncogenetic protein enhancer of zeste homolog 2 (EZH2) and miRNA-449a, which down-regulates histone deacetylase 1 (Varambally et.…”
Section: Mirnas and Epigenetic Control Of Pcamentioning
confidence: 99%
“…Numerous miRNA host genes as well as miRNAs promoters are epigenetically regulated in prostate cancer (36,66). For instance miR-193b and miR-34a are tightly controlled by promoter methylation in PCa (9).…”
Section: Discussionmentioning
confidence: 99%
“…Only recently, investigations have awakened attention to the interplay between AR and microRNAs (miRNAs or miRs) (5)(6)(7)(8). Like many protein-coding genes, miRNAs are under control of transcription factors as well as epigenetic mechanisms whose deregulation leads to a loss or gain of miRNA function with possible implications in tumorigenesis (9,10). miRNAs are short, noncoding, single-stranded RNAs that potentially regulate hundreds of mRNAs.…”
mentioning
confidence: 99%
“…Surprisingly, miRNAs are also mediators of androgen action. 19,26,27 In PCa, AR can function in two opposite directions: 28 on one side, AR signaling is crucial for prostate and PCa cell survival; 29 however, its activation can also limit cell proliferation and mediate apoptotic induction under specific circumstances, 28,29 like in conditions of genotoxic stress, when AR is fundamental for p53 activation and for the subsequent induction of apoptosis. Even though androgens increase the expression of a large set of miRNAs, clinically only a few miRNAs mediate androgen action in prostate.…”
Section: Prostate Cancerogenesis In the Context Of Preexisting Male Imentioning
confidence: 99%
“…25 Epigenetic regulation of androgen receptivity is also modulated by miRNA While in some cases, AR is not functional because of genetic mutations, it has been found in almost 40% of PCa patients (like in DU145 cell line) to be silenced by promoter hypermethylation. 19,26,27 In PCa, AR can function in two opposite directions: 28 on one side, AR signaling is crucial for prostate and PCa cell survival; 29 however, its activation can also limit cell proliferation and mediate apoptotic induction under specific circumstances, 28,29 like in conditions of genotoxic stress, when AR is fundamental for p53 activation and for the subsequent induction of apoptosis. 30,31 A new study has found at least 71 miRNAs affecting the AR expression in PCa cell lines, 13 of them directly binding to and regulating its 6-kb extended 3′-UTR.…”
Section: Prostate Cancerogenesis In the Context Of Preexisting Male Imentioning
confidence: 99%